Stage-specific and regional trends in prostate cancer incidence in Kazakhstan, 2005–2024 - Igissinova, Gulnur; Igissin, Nurbek; Kudaibergenova, Indira; Yermek, Nariman; Telmanova, Zhansaya; Turebayev, Dulat; Jexenova, Akzhunis; Moldagali, Rustem; Khairli, Gafur; Kazhitaev, Almas; Dyakov, Sergey; Baibosynov, Daulet; et al. (Frontiers in Oncology, 2025)
BackgroundProstate cancer is a leading malignancy among men globally and continues to be a growing concern in Kazakhstan, where evidence regarding its long-term epidemiological trends is limited.ObjectivesThis study seeks to assess national and regional trends in prostate cancer incidence, stage distribution, and morphological verification in Kazakhstan from 2005 to 2024.MethodsA nationwide observational study utilizing registry data from the Unified Nationwide Electronic Health System was performed. Incident cases (ICD-10 code C61) were examined according to age, geographical region, and stage at diagnosis. The incidence rates were adjusted to the WHO World Standard Population (2000–2025) by age. Joinpoint regression was used to look at temporal trends, and it showed the annual percent change (APC) and the average annual percent change (AAPC) with 95% confidence intervals.ResultsFrom 2005–2024, 21,756 prostate cancer cases were recorded, with a mean age at diagnosis of 69.8 years. The age-standardized incidence rate (ASR) increased from 11.9 to 20.7 per 100,000 men (APC = +2.6%, p = 0.002). Four distinct periods were identified: an early decline (2005–2008), a sharp rise (2008–2016), a downturn (2016–2020), and a renewed increase (2020–2024). Age-specific incidence was negligible below 50 years, peaking at 75–79 years (228.6 per 100,000). Regional analyses revealed heterogeneous trends: monotonic increases in Atyrau, Aktobe, and Almaty (region), contrasted by boom–dip–rebound profiles in Karaganda, Pavlodar, and Almaty City. The proportion of early-stage (I–II) cases rose from 32.8% to 56.9%, while stage III declined from 49.7% to 22.9%; stage IV increased slightly (17.3% → 20.2%). Morphological verification improved nationally (mean ≈ 92%) and plateaued after 2015.ConclusionsKazakhstan shows an increase in prostate cancer cases, with more cases being diagnosed at an earlier stage but still a lot of cases being diagnosed at a later stage. This is probably due to the PSA screening program from 2013 to 2017, changes in policy since then, and problems with diagnosis during the pandemic. To get better results, we need to improve early detection, timely biopsy pathways, and connections to mortality and survival data.